Bidirectional Interference Between Speech and Nonspeech Tasks in Younger, Middle-Aged, and Older Adults. - Bailey, Dallin J.; Dromey, Christopher (Journal of Speech, Language & Hearing Research, 2015)
Purpose: The purpose of this study was to examine divided attention over a large age range by looking at the effects of 3 nonspeech tasks on concurrent speech motor performance. The nonspeech tasks were designed to facilitate measurement of bidirectional interference, allowing examination of their sensitivity to speech activity. A cross-sectional design was selected to explore possible changes in divided-attention effects associated with age. Method: Sixty healthy participants were separated into 3 groups of 20: younger (20s), middle-aged (40s), and older (60s) adults. Each participant completed a speech task (sentence repetitions) once in isolation and once concurrently with each of 3 nonspeech tasks: a semantic-decision linguistic task, a quantitative-comparison cognitive task, and a manual motor task. The nonspeech tasks were also performed in isolation. Results: Data from speech kinematics and nonspeech task performance indicated significant task-specific divided attention interference, with divided attention affecting speech and nonspeech measures in the linguistic and cognitive conditions and affecting speech measures in the manual motor condition. There was also a significant age effect for utterance duration. Conclusions: The results increase what is known about bidirectional interference between speech and other concurrent tasks as well as age effects on speech motor control.